2009
DOI: 10.1186/1472-6807-9-57
|View full text |Cite
|
Sign up to set email alerts
|

Low-resolution structural studies of human Stanniocalcin-1

Abstract: Background: Stanniocalcins (STCs) represent small glycoprotein hormones, found in all vertebrates, which have been functionally implicated in Calcium homeostasis. However, recent data from mammalian systems indicated that they may be also involved in embryogenesis, tumorigenesis and in the context of the latter especially in angiogenesis. Human STC1 is a 247 amino acids protein with a predicted molecular mass of 27 kDa, but preliminary data suggested its di-or multimerization. The latter in conjunction with al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 75 publications
2
21
0
Order By: Relevance
“…To validate the integrity of the protein, we analyzed the disulfide pairing by subjecting tryptic peptides separated by reversed-phase chromatography to MALDI mass spectrometry (Table 1). Determined masses of isolated peptides are in agreement with the previously published data on the disulfide structure of human (38) and salmon (39) STC1, for which five intramolecular bonds (Cys-45-Cys-59, Cys-54 -Cys-74, Cys-65-Cys-114, Cys-98 -Cys-128, and Cys-135-Cys-170) and one intermolecular bond (Cys-202-Cys-202) were demonstrated. However, we also identified a peptide containing a cysteinylated variant of Cys-202 (Table 1 and Fig.…”
Section: Stc1 Inhibits the Proteolytic Activity Of Papp-a -To Test Thesupporting
confidence: 87%
“…To validate the integrity of the protein, we analyzed the disulfide pairing by subjecting tryptic peptides separated by reversed-phase chromatography to MALDI mass spectrometry (Table 1). Determined masses of isolated peptides are in agreement with the previously published data on the disulfide structure of human (38) and salmon (39) STC1, for which five intramolecular bonds (Cys-45-Cys-59, Cys-54 -Cys-74, Cys-65-Cys-114, Cys-98 -Cys-128, and Cys-135-Cys-170) and one intermolecular bond (Cys-202-Cys-202) were demonstrated. However, we also identified a peptide containing a cysteinylated variant of Cys-202 (Table 1 and Fig.…”
Section: Stc1 Inhibits the Proteolytic Activity Of Papp-a -To Test Thesupporting
confidence: 87%
“…It has previously been shown that 10 of these form five intramolecular disulfide bonds, and that one residue is responsible for dimerization (38). These 11 cysteine residues are conserved in STC2, which contains three additional cysteines, Cys-120, Cys-197, and Cys-205 (Fig.…”
Section: Abilities Of Stc2 To Covalently Bind and Inhibit Papp-a And mentioning
confidence: 99%
“…A cytochrome c-type CXXCH motif is present rather than the typical HRM (45)(46)(47)(48). Further studies are also required to establish the physiological relevance of the apparent heme-mediated inhibition of the arginine transferase activity of R-transferase and of putative heme binding to stanniocalcin glycoprotein hormones (52)(53)(54). For DGCR8, heme may have a structural role, although a heme redox state dependence on RNA binding was proposed (50,51 …”
Section: Non-nr Heme Sensorsmentioning
confidence: 99%
“…Heme binding was proposed to occur at a CS (not CP) motif. However, it was also reported that this Cys forms a disulfide and does not bind heme (53,54) and that STC1 may operate a thiol/disulfide redox switch, as described above (54). HRM-containing heme sensors are summarized in Table 1.…”
Section: Cellular Homeostasismentioning
confidence: 99%